Refugee issues in the 21st century: challenges to humanity and world diplomacy - Salawati Mat Basir,; Saidatul Nadia Abd Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The current flow of human beings escaping their countries’ turmoil is not a temporary surge or a passing crisis. Mass migration, accompanied by sudden surges of people, will be a permanent challenge to 21st century states and world order. Recent surges of refugee and asylum claimants are testing the capacity of states and eroding traditions of welcome in receiving countries for refugee and migrants alike. At the same time, the intersection of forced migration, human rights, and conflict presents a unique challenge for world foreign policy in this 21st century. These three factors are already beginning to combine in ways that undermine traditional understandings of national security and offer ample reason to revisit traditional divisions of labour between diplomacy, defence, economic social development policy around the world. Accordingly, this paper has three objectives. Firstly, this paper provides a brief overview of refugee issues in the 21st century with major issue of forced migration, human rights, and conflict and its implications. Secondly, this paper highlights emergent issues and challenge faced by the countries around the world regarding refugees and humanity. Thirdly, this paper discusses the challenge of world diplomacy when it comes to the issue of refugee and humanity. Finally, the paper will highlights the ways in which world foreign policy must adapt to meet the challenges they facing today regarding this issue.